2008
DOI: 10.1038/nature07578
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia causes fragmentation of the Golgi compartment to ensure reproduction

Abstract: The obligate intracellular bacterium Chlamydia trachomatis survives and replicates within a membrane-bound vacuole, termed the inclusion, which intercepts host exocytic pathways to obtain nutrients. Like many other intracellular pathogens, C. trachomatis has a marked requirement for host cell lipids, such as sphingolipids and cholesterol, produced in the endoplasmic reticulum and the Golgi apparatus. However, the mechanisms by which intracellular pathogens acquire host cell lipids are not well understood. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
277
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(293 citation statements)
references
References 26 publications
13
277
3
Order By: Relevance
“…Using the Golgi markers, GM130 and b-COP we found that virus infection results in Golgi fragmentation and dispersion. The breakdown and dispersal of the Golgi stacks has been reported to lower the efficiency of protein export [29] and can facilitate the replication of some intracellular pathogens [13]. Herpes Simplex Virus-1-induced Golgi fragmentation has been found to increase the efficiency of virion release into the extracellular space [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the Golgi markers, GM130 and b-COP we found that virus infection results in Golgi fragmentation and dispersion. The breakdown and dispersal of the Golgi stacks has been reported to lower the efficiency of protein export [29] and can facilitate the replication of some intracellular pathogens [13]. Herpes Simplex Virus-1-induced Golgi fragmentation has been found to increase the efficiency of virion release into the extracellular space [5].…”
Section: Discussionmentioning
confidence: 99%
“…NOC inhibits microtubule polymerization which leads to trans-Golgi network fragmentation, whereas BFA disrupt the anterograde transport, and forms the trans-Golgi tubular network [9]. ZWEHD is an inhibitor of inflammatory caspases and inhibits Golgi fragmentation [13]. These inhibitors of vesicle function and integrity reduce virus replication as evidenced by a reduction in virus titer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fragmentation of the Golgi in HCV correlates with the decrease in general secretory capacity of the infected cell but further implicates the organelle in important viral processes and hints toward sequestration of secretory components at sites of viral assembly. Golgi disruption and decrease in secretory capacity of host cells is a peculiar feature of many infectious agents such as Chlamydia, poliovirus, and rhinovirus 1A, where the Golgi membranes serve an important role in viral replication and morphogenesis (57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of Rab11a, using a dominant negative form which cannot tether to the ApV, they attenuate A. phagocytophilum intracellular survival by >10% at 5 h post-infection in HL-60 cells [191]. RNAi knockdown of Rab11a in HeLa and HEp-2 cells, prevents Chlamydia trachomatis reversion from the metabolically active reticulate body into the inert infectious elementary body by blocking the bacteria's ability to disrupt the Golgi [245][246][247]. Excitingly, when we re-visited the Coxiella burnetii genome-wide RNAi screen data (another pathogen residing in a pathogen containing vacuole termed the CCV) we noticed that inhibition of Rab11b also prevented bacterial replication [131].…”
Section: Anaplasma Phagocytophilum-occupied Vacuole (Apv) Within 5 Hmentioning
confidence: 99%